(untitled) (Praxis Educativa, 2025)
The article addresses the complex and conflictive relationship between the National Scientific and Technical Research Council of Argentina and its relationship with the public university, based on a socio-historical journey that begins with the creation of the Council in 1958 until the beginning of the current one. democratic cycle. In this trajectory addressed sequentially and ordered by the institutional changes that occurred in Conicet, the historical and political framework is intertwined, as well as the relationships between the Council and the higher education system.